Advanced dose calculation algorithms in lung cancer radiotherapy: Implications for SBRT and locally advanced disease in deep inspiration breath hold. (December 2018) - Josipovic, Mirjana; Persson, Gitte Fredberg; Rydhög, Jonas Scherman; Smulders, Bob; Thomsen, Jakob Borup; Aznar, Marianne Camille
Highlights: Dose to the lung tumours differed when AAA plans were recalculated with AcurosXB. AAA overestimated dose especially at the edge of the PTV, compared to AcurosXB. Algorithm differences were larger in SBRT than in locally advanced treatment plans. Most differences between the algorithms increased in deep inspiration breath hold. Dose to the risk organs did not differ substantially between the algorithms. Abstract: Purpose: Evaluating performance of modern dose calculation algorithms in SBRT and locally advanced lung cancer radiotherapy in free breathing (FB) and deep inspiration breath hold (DIBH). Methods: For 17 patients with early stage and 17 with locally advanced lung cancer, a plan in FB and in DIBH were generated with Anisotropic Analytical Algorithm (AAA). Plans for early stage were 3D-conformal SBRT, 45 Gy in 3 fractions, prescribed to 95% isodose covering 95% of PTV and aiming for 140% dose centrally in the tumour. Locally advanced plans were volumetric modulated arc therapy, 66 Gy in 33 fractions, prescribed to mean PTV dose. Calculation grid size was 1 mm for SBRT and 2.5 mm for locally advanced plans. All plans were recalculated with AcurosXB with same MU as in AAA, for comparison on target coverage and dose to risk organs. Results: Lung volume increased in DIBH, resulting in decreased lung density (6% for early and 13% for locally-advanced group). In SBRT, AAA overestimated mean and near-minimum PTV dose (p-values < 0.01) compared to AcurosXB, with largest impact in DIBH (differences of up to 11 Gy). These clinically relevant differences may be a combination of small targets and large dose gradients within the PTV. In locally advanced group, AAA overestimated mean GTV, CTV and PTV doses by median less than 0.8 Gy and near-minimum doses by median 0.4–2.7 Gy. No clinically meaningful difference was observed for lung and heart dose metrics between the algorithms, for both FB and DIBH. Conclusions: AAA overestimated target coverage compared to AcurosXB, especially in DIBH for SBRT.